Antibiotic susceptibility profile and extended spectrum β-lactamases production by uropathogenic Escherichia coli from tertiary care hospital of rural settings - Rahman, Mustafa Sofiur; Garg, Ritu; Singh, Varsha A.; Biswas, Dipankar (International Journal of Research in Medical Sciences, 2018)
Background: Escherichia coli are the most common cause of urinary tract infections in community as well as hospital settings. Emergence of drug resistance in Escherichia coli due to various mechanisms makes the treatment options very limited. This study was undertaken to detect ESBLs in uropathogenic Escherichia coli isolates and to determine their antimicrobial susceptibility pattern in rural setting. Methods: A prospective study was done on 502 E. coli isolates from clinically suspected cases of urinary tract infections (UTI) patients of all age groups. All samples were inoculated on Cysteine Lactose Electrolyte Deficient Agar (CLED). Organisms grown in pure culture were identified by standard biochemical tests. Antibiotic susceptibility test was done by the Kirby Bauer Disc diffusion method on Muller Hinton agar. ESBL detection was done as per CLSI guidelines. Results: Of the 502 isolates of Escherichia coli, nitrofurantoin (82%) was found be most sensitive antimicrobial followed by amikacin (73%), gentamycin (71%) and imipenem (64%). Common empirically used antibiotics like fluroquinolones and Cotrimoxazole drugs showed alarming rate of resistance. 60% isolates were found to be multidrug resistant. ESBL production was detected in 31% isolates. ESBL producing strains were found to be more drug resistant than non ESBL producing strains. Conclusions: So, drug resistance due to production of ESBLs in Escherichia coli is a serious threat for clinicians. Strict infection control measures and early detection of beta lactamase producing isolates are the need of the hour to contain the emergence of this type of resistance.